Removal of Acidic Dyes from Aqueous Media Using Citrullus Lanatus Peels: An Agrowaste-Based Adsorbent for Environmental Safety. (13th March 2019) - Latif, Shoomaila; Rehman, Rabia; Imran, Muhammad; Iqbal, Shahid; Kanwal, Ayesha; Mitu, Liviu
Abstract : In this work, removal of fluorescein and eosin dyes using common agrowaste, i.e., peels of water melon ( Citrullus lanatus ) (WMP), has been studied in the batch mode. The sorbent material (WMP) was characterized by using scanning electron microscopy, Fourier transform infrared spectroscopy, thermogravimetric analysis, and elemental analysis. The sorbent was chemically modified by subjecting it to 0.1 N HNO3 and 0.1 N NaOH solutions. Different parameters such as sorbent dose, pH, temperature, and agitation speed were optimized to investigate the sorbent efficiency for fluorescein and eosin dyes. Among three forms (raw, base-treated, and acid-treated), the base-treated form exhibited higher removal efficiency, followed by acid-treated and then the raw form. Generally, range for the removal of fluorescein and eosin was found to be 48.06–88.08% and 48.47–79.31%, respectively. Mathematical modeling of sorption data by Langmuir and Freundlich sorption isotherms and thermodynamic investigations were carried out to check the suitability of these agrowaste materials on bulk scale. The promising results concluded that peel of water melon (common agrowaste) can be potentially utilized for the removal of toxins.